Final-Year Medical Students’ Perceptions Regarding the Curriculum in Public Health - Navinan, Mitrakrishnan Rayno (Medknow Publications & Media Pvt Ltd, 2011)
BACKGROUND: The Faculty of Medicine, University of Colombo, has an integrated curriculum in which teaching of public health takes place through a series of modules which span the full five-year study programme. AIM: To assess final year medical student perceptions regarding the public health curriculum and to identify factors which influence this. MATERIALS AND METHODS: The study was cross sectional. Convenience sampling was utilized on final-year students of the Faculty of Medicine, University of Colombo, Sri Lanka. A self-administered 4-point Likert scale questionnaire covered general opinion on public healthcare and perceptions about the curriculum. Data were analyzed using descriptive statistics and Chi-square tests. RESULTS: One hundred and eighty four students (94%) participated in the study. Eighty-two percent (148) viewed public health as an important field. Only 9% (16) were interested in a career in public health. A significant association was found between choosing public health as career and the following: perception of public health as an important field; holding a good opinion about public health prior to commencement of the course; having found the field-based experience enjoyable and beneficial to the community; and feeling competent to work in the community at the end of the course (P < 0.01). With regard to teaching methods, group activities and discussion-centered activities were identified positively (153, 83% and 125, 68% respectively). The majority of students indicated that they were not stimulated to read more on the subject or regularly revise what they have learnt, both during the introductory public health programme and during the final year. CONCLUSIONS: The curriculum has been able to create a positive opinion about public health. However, students lack enthusiasm to learn independently. Experiential, group-centered teaching activities and a constructivist approach may be more effective in promoting independent learning. Perceptions are important and should aid in structuring the curricula.